Un cadre analytique pour étudier l’impact économique des autoroutes interurbaines : une application à la région de Montréal - Polèse, Mario; Thibodeau, Jean-Claude (L'Actualité économique, 1975)
AbstractIn this paper, the authors propose a framework which enables them to analyse the economic impact of new highway links between Montreal and eleven surrounding cities, specifically the impact on the economic structure of those cities. The authors observe a relationship between changes in accessibility (to Montreal) and economic structure. Greater accessibility resulting from new highway construction seems generally to favour industrial growth and diversification, although a very rapid and radical change in accessibility can also have negative consequences on the short run. The service sector appears particularly sensitive to changes in accessibility. The authors observe a cut off point of one hour's travel time: as soon as city falls within this travel-time zone its service sector (especially more the sophisticated services) systematically declines. Finally, the authors conclude that the precise nature of the impact of increased accessibility to Montreal is largely a function of the original economic structure of the city concerned: certain structures are more sensitive to changes in accessibility than others.